The Transit-Oriented Development Model in Montreal (Canada): Mobilizing a Concept and Negotiating Urban Development at the Local and Metropolitan Scale - Cournoyer-Gendron, Maude (Environnement urbain)

(untitled) (Institut National de Recherche Scientifique Centre Urbanisation Culture et Société, 2017)
The concept of transit-oriented development (TOD) has now become a fixture in planning documents of metropolitan areas around the world. Looking at the Greater Montreal area, this article discuss the recontextualisation of the (abstract) idea of TOD and the specific ways in which it has been defined, implemented and used by local and metropolitan actors. Set up into a centerpiece of the dominant discourse in metropolitan planning, the TOD also serves as a mean of negotiation and legitimization for local elected officials in a context of multi-layered governance.